Pendugaan Biomasa Karbon di Atas Tanah Pada Tegakan Rhizophora Mucronata di Ciasem, Purwakarta - I Wayan Susi Dharmawan (Institut Pertanian Bogor, 2010)
Indonesia has a lot of potential natural forests, whether still intact or logged forest. Hish concentration of C02 in atmosphere is one of the factors which cause global climate change in the world. Development and maintenance of forest vegetation such as mangrove forest is one of waysreducing atmhosper Rhizophora biomass stand was conducted. The research was implemented at BPKH Ciasem, KPH Purwakarta, Perum Perhutani unit III Jawa Barat and Banten. From the destructive sampling activity in the field the following allometric models was obtained for above ground biomass Y = 0,1466(DBH)2,3136 (R2=0,936). Stand of Rhizophora mucronata at BKPH Ciasem had potency of above ground biomass and above ground carbon content of 77.2 ton/ha and 38.6 ton/ha, respectively. Related with above ground biomass, the uptake of CO2 and uptake of average C02 of Rhizophora mucronata were 141.5 ton/ha and 0.251 ton/tree.